2007
DOI: 10.1111/j.1365-2664.2007.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

The relative effects of raptor predation and shooting on overwinter mortality of grey partridges in the United Kingdom

Abstract: Summary 1.Factual information is key to resolving conflicts between raptor conservation and gamebird management, especially when the conservation status of one of the species involved is threatened. The grey partridge Perdix perdix is a UK Biodiversity Action Plan species because of a marked decline in abundance caused by agricultural intensification. Recently, the number of raptors present on farmland and the commercial shooting of red-legged partridges Alectoris rufa have both increased. To inform conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 18 publications
2
36
0
3
Order By: Relevance
“…Apparent competition between ring-necked pheasants and grey partridges, mediated via the caecal nematode, may be one cause of the recent decline in UK grey partridge numbers and may be hampering current efforts to re-establish and increase wild populations (Tompkins et al 2001(Tompkins et al , 2000a. Releasing pheasants and red-legged partridges also leads to unsustainable heavy losses of grey partridges by shooting as they inadvertently become caught up in the drives of released gamebirds (Watson et al 2007). As a result, grey partridge numbers decreased more on estates with game bird releasing compared to estates with no releasing (Aebischer and Ewald 2004).…”
Section: Population Changes Before 1950mentioning
confidence: 96%
See 1 more Smart Citation
“…Apparent competition between ring-necked pheasants and grey partridges, mediated via the caecal nematode, may be one cause of the recent decline in UK grey partridge numbers and may be hampering current efforts to re-establish and increase wild populations (Tompkins et al 2001(Tompkins et al , 2000a. Releasing pheasants and red-legged partridges also leads to unsustainable heavy losses of grey partridges by shooting as they inadvertently become caught up in the drives of released gamebirds (Watson et al 2007). As a result, grey partridge numbers decreased more on estates with game bird releasing compared to estates with no releasing (Aebischer and Ewald 2004).…”
Section: Population Changes Before 1950mentioning
confidence: 96%
“…Important to note in these studies is that hunting mortality (albeit sometimes strongly reduced) remained next to predation an important mortality factor. The mortality caused by hunting (35-39%) in some areas in the UK was more than double the losses caused by raptor predation (9.5-15%; Watson et al 2007).…”
Section: Population Changes Before 1950mentioning
confidence: 98%
“…In the study reported here, the defecation behaviour of the grey partridge (Perdix perdix) was examined at night time and discussed in the context of predator avoidance behaviour against the background of a night-time environment dominated by the risk of predation by the red fox (Vulpes vulpes). Watson et al (2007) estimate that fox predation accounts for 44% of the natural mortality of the grey partridge during winter. This high mortality is despite measures undertaken to reduce the number of foxes and the well-known anti-predation measures adopted by partridges to avoid predation by foxes, which hunt at night using scent.…”
Section: Introductionmentioning
confidence: 99%
“…Reynolds & Tapper 1995b), is regarded by game managers or hunting groups throughout the country as the main cause of decline of populations of small game (Vargas & Muñoz 1996). Intensive fox culling programmes in Spain are largely undertaken within those estates dedicated to hunting of rabbits and partridges, with frequent game restocking, and hence intensively managed (Watson et al 2007, Beja et al 2009). Removal of foxes affects productivity (Heydon & Reynolds 2000, López-Martín et al 2007, as well as the spatial dynamics of populations (Von Schantz 1981, Reynolds 2000.…”
Section: Introductionmentioning
confidence: 99%